Strategies for New Students of Islamic Boarding School Alumni in Overcoming Culture Shock in Higher Education - Arif Hamdi; Fitriah M. Suud (AFKARINA: Jurnal Pendidikan Agama Islam, 2026)
Differences in learning ecology, social interaction patterns, and culture between Islamic boarding schools and universities often lead to culture shock among new students who are alumni of Islamic boarding schools. This condition not only impacts psychological aspects but also influences the academic and social adjustment process. This study aims to examine the adaptation strategies used by new students who are alumni of Islamic boarding schools in dealing with these conditions in higher education. The method used is a qualitative approach with a descriptive research type. The research subjects consisted of 20 new students who were alumni of Islamic boarding schools selected through a purposive sampling technique. The results show that students experience three main forms of culture shock: changes in learning systems and relationship patterns, the existence of stereotypes regarding identity, and shifts in views regarding gender roles. To overcome these, students develop various adaptation strategies, including academic strategies such as independent learning and self-regulated learning, social strategies through strengthening relationships and communication, cultural strategies in the form of identity negotiation, and psychological strategies such as resilience, self-reflection, and intrinsic motivation. These findings indicate that culture shock is not only an obstacle but also plays a role in the transformation process that strengthens students' academic and social identities.